Capo Granitola-Sciacca Fault Zone (Sicilian Channel, Central Mediterranean): Structure vs magmatism. (September 2018) - Civile, Dario; Lodolo, Emanuele; Accaino, Flavio; Geletti, Riccardo; Schiattarella, Marcello; Giustiniani, Michela; Fedorik, Jakub; Zecchin, Massimo; Zampa, Luigi
Abstract: The tectonic framework of the northern sector of the Capo Granitola-Sciacca Fault Zone (CGSFZ), a NNE-oriented lithospheric strike-slip fault zone located in the Sicilian Channel (southern Italy), has been reconstructed with the aim to clarify the relationships between geometry and kinematics of the structures and the occurrence and distribution of the magmatic manifestations observed in the area. This has been achieved by the interpretation of a large dataset composed of 2-D multichannel seismic profiles, Chirp profiles, magnetic data and borehole information. In addition to the volcanic edifices known in the Graham and Terribile banks, this study has allowed to recognize several other magmatic manifestations. The magmatic occurrences consist of small volcanic cones, buried magma ascents and potential igneous sills. The CGSFZ is bounded by two strike-slip fault systems, the Capo Granitola Fault System (CGFS) to the west and the Sciacca Fault System (SFS) to the east, dominated by positive flower structures generated by tectonic inversion of NNE-oriented late Miocene extensional faults. Only the southern part of the CGFS shows the presence of a sub-vertical, N-S oriented strike-slip master fault. The sector between the two fault systems does not show a significant Pliocene-Quaternary tectonic deformation, except for its southern part hosting the Terribile Bank, which is dissected by WNW to NW-trending normal faults developed during late Miocene and later reactivated. This set of faults is currently active at the Terribile Bank, whereas is buried by Pliocene-Quaternary deposits in the central and northern sectors of the CGSFZ. The observed magmatism is driven by a mechanism of non-plume origin. Magmas have used as open paths the faults of the CGFS and SFS, which cut the whole lithosphere reaching the asthenosphere and producing partial melting by simple pressure release. Most of the magmatism develops along the strike-slip master fault associated with the CGFS and the normal faults affecting the Terribile Bank. The magmatic feeding of the Terribile Bank would be related to lateral magma migration coming from the structures of the SFS, which would use the open pathways represented by active normal faults. In the central-northern part of the CGSFZ, magmas migrate upward along lithospheric faults, then move laterally and rise toward the surface through NNE and NW-trending buried normal faults. These late Miocene faults do not reach the surface, and this may have favoured the emplacement of igneous sills, which in turn may explain the observed volcanic centres. Highlights: A structural map of the northern part of the Capo Granitola-Sciacca strike-slip Fault Zone (Sicilian Channel) has been produced. Numerous magmatic manifestations in addition to those already known in the Graham and Terrible banks, have been recognized. A relationship between magmatism and structures associated with the Capo Granitola-Sciacca Fault Zone, has been documented. A mechanism of non-plume origin is proposed for the magmatism observed in the study area.